HIDDEN STRATEGIES FOR MASTERING A FOREIGN LANGUAGE QUICKLY: SCIENCE-BACKED METHODS FOR EFFORTLESS LEARNING (INTERNATIONAL JOURNAL OF SCIENCE AND TECHNOLOGY, 2025)
This paper presents a micro-level empirical study on strategic vocabulary acquisition tailored to learners’ individual interests. Drawing on the foundational theories of second language acquisition (SLA), including Krashen’s Input Hypothesis and Gardner’s Theory of Multiple Intelligences, this study explores how personalized, interest-based methods can significantly enhance vocabulary retention and practical usage. Three IELTS learners with different interests—films, music, and books—participated in an eight-week experimental program. The findings indicate that contextual and emotionally engaging input leads to superior vocabulary acquisition and speaking fluency. This research contributes to the growing body of literature advocating for learner-centered methodologies and supports integrating cognitive psychology and personalized content in ESL classrooms.